Dental and Gingival Status of 5 and 12-Year-Old Children in Jakarta and Its Satellite Cities - Adiatman, Melissa; Yuvana, Afida Luthfi; Nasia, Avina Anin; Rahardjo, Anton; Maharani, Diah Ayu; Zhang, Shinan (Journal of Dentistry Indonesia, 2016)
Jakarta is the capital city of Indonesia which is surrounded by its satellite cities Bogor, Depok, Tangerang, Bekasi. Nonetheless, scarce information are available of the current oral health of children. Objective: The study aims to describe caries and gingival status among 5 and 12 years old children in Jabodetabek. Jabodetabek is an abbreviation of Jakarta, the capital city of Indonesia, and the satellite cities in its surrounding (Bogor, Depok, Tangerang, Bekasi). Methods: The survey was done in 2014 and had already got ethical approval. Design of this study was crosssectional. Subjects were 5-year-old and 12-year-old Indonesian children living in Jabodetabek, selected using cluster sampling method. One trained examiner performed the clinical examination. Caries experience was measured using DMFT index, severity of decayed teeth was assessed using PUFA index, gingival status and oral hygiene were measured by Loe and Sillness modified index. Results: A total of 390 5-year-old and 458 12-year-old children with balanced proportion between girls and boys participated in the survey. The prevalence of caries experience among the 5-yearold children and 12-year-old children were 90% and 84% respectively. The mean DMFT and DT scores among the 5-year-old children and 12-year-old children were 7.5±5.5 and 6.8±4.8; 3.2±2.2 and 2.9±2.1 respectively. Pulp involvement were apparent in 45% and 23% of caries in 5 and 12-year-old children respectively. Most children, 45% 5-year-old children and 92% 12-year-old children had substantial amount of plaque. Moreover, 68% 12-year-old children had gingivitis. Conclusion: Dental caries were prevalent among 5 and 12-year-old Indonesian children in Jakarta and its satellite cities. The oral health condition of most of the children were poor